Efeito da carga orgânica volumétrica sobre a produção de biogás utilizando-se dejeto de suíno em diferentes configurações de reatores anaeróbios - Lins, Marcos Araújo (2017)
The use of anaerobic reactors with energetic purposes is an effective decision-making to treat swine farming wastewater. But, the applied organic loading rate (OLR)must be correct, since itvaries according to the reactor configuration and other process conduction conditions, such as temperature. Thus, this trial aimed at showing the effect of OLR progression on biogas generation and quality of swine manure in anaerobic reactors as continuous stirred tank reactor (CSTR), covered lagoon digester (CLD) and upflow anaerobic sludge blanket (UASB).The experiment with CSTR reactor of 17-L useful volume, semicontinuously fed at 37 ± 1 °C, was divided into three phases. In the first phase, a constant OLR was applied with 1.0 g VS add L-1reactor d-1 until biogas productivity was stable. This occurred after the fortieth day of operation. In phase II, the OLR progressions had begun, starting with 2.0 g VS add. L-1reactor d-1 and after stabilizing biogas production rate, OLR was increased to 3.0 g VS add. L-1 reactor d-1. In phase III, OLR answers were 1.0, 1.9 and 0.7 g Vs add. L-1reactor d-1 and submitted in this order, according to the hydraulic retention time (HRT) in order to identify the relation among these variables. In the trial with CLD of 17-L useful volume, and semicontinuously fed, OLR answers were 0.3, 0.4 and 0.5 g VSadd. L-1reactor d-1, respectively. The experiment with theUASB reactor of 6.6-L useful volume, continuously fed at 37 ± 1 °C, was divided into two phases. In phase I, OLR answers were:1.5, 2.0, 2.5 and 3.0 g VSadd L-1reactor d-1. In phase II, OLR answers were 0.5, 0.7, 1.0, 1.4, 1.6, 2.2, 2.9 and 8.4 g VS add. L-1reactor d-1.For CSTR reactor, the best results of methane content and biogas production rate was in OLR 1.9 g VS add. L-1reactor d-1 and HRT of 15 days, with 53 ± 10% (v v-1) and 0.7 ± 0.1 LNbiogas L-1reactord-1, respectively. In the experiment with CLD reactor, the best results of methane content and biogas production rate was in OLR 0.5 g VS add L-1reactor d-1 and HRT of 34 days, with 61 ± 5% (v v-1) and 0.3 ± 0.1 LN biogas L-1reactor d-1, respectively. For the UASB reactor, the best result of methane content and biogas production rate was in OLR 2.9 g VS add. L-1reactor d-1 and HRT of 1.5 days, with 74 ± 1% (v v-1) and 1.6 ± 0,5 LN biogas L-1reactor d-1, respectively. This research aimed at understanding the effect of OLR progression on the biogas production rate up from DS, establishing a relation among other variables that affect this biofuel production, contributing with important information to choose the most available reactor configuration to be settled in a full scale.